Taking sides clashing views on controversial issues in drugs and society - Goldberg, Raymond (McGraw-Hill/Dushkin, 2002)
Is a debate-style reader designed to introduce students to controversies in drug use and misuse in contemporary society. The reading, which present the arguments of leading social scientists, health care professionals, and social commentators, reflect a variety of viewpoints and have been selected for their liveliness and substance and because of their value in debate framework. For each issue, the editor provides a concise introduction and postscript summary. The introduction sets the stage for the debates as it is argued in the "yes" and "no" readings, and the postscript briefly reviews the opposing views and suggests additional readings on the controversial issue under discussion.--Cover.